Migration and Knowledge Diffusion: The Effect of Returning Refugees on Export Performance in the Former Yugoslavia - Hauptmann, Andreas; Ozguzel, Cem; Rapoport, Hillel; 2024; Bahar, Dany (The Review of Economics and Statistics, 2024)
During the early 1990s, Germany offered temporary protection to 700,000 Yugoslavian refugees fleeing war. By 2000, many had been repatriated. We exploit this natural experiment to investigate the role of returning migrants in boosting export performance upon their return. Using confidential German administrative data, we find that industries with 10% more returning refugees exhibit larger exports between the pre- and postwar periods by 1% to 1.6%. We use exogenous allocation rules for asylum seekers within Germany as an instrument to deal with endogeneity concerns. We show evidence pointing to productivity shifts as the main mechanism behind our results. Consistently, we find our results are driven by refugees in occupations more likely to transfer knowledge, technologies, and best practices.
Keywords: German Labor Force; Refugee Crisis; Yugoslavian Refugees; Yugoslavian Workers; Migration